Puntos críticos sanitario en la comercialización de la banda negra Myloplus schomburgkii Jardine & Schomburk 1841 y su influencia en los problemas sanitarios - Ruiz Vasquez, Carlos Manuel (2024)
The management and commercialization of ornamental fish is the third most important activity in the Peruvian Amazon. However, for the success of the export, it is necessary to consider the technical and operational aspects, because a bad practice in routine tasks could trigger health problems, such as the presence of parasites, making it difficult for them to adapt during storage, thus limiting success. of export. The objective of this research was to identify the critical points in the commercialization of Myloplus schomburgkii “black-band myleus” and its influence on the presence of health problems. The analysis of the study variables was in a real context, that is, the variables were not manipulated and consisted of visiting fishermen, collectors and aquarists to gather information through interviews regarding the activities of capture, management and marketing of the “black-band myleus”. Likewise, in a complementary way, the parasitological analysis of 30 individuals of “black-band myleus” collected by each commercialization stage was carried out for the analysis of the main parasitic indices.